An Exploratory Study on the Level of Trust Towards Online Retailers in United Kingdom and Malaysia - Wazeer, Mohamed Wazni (2005)
The inspiration for this project was profoundly influenced by a publication written by P.Michell and his expert collaborators (1998). It masterfully introduces the foundations to the burgeoning field of Trust. It covers all aspects associated with trust, identifying twenty-two variables through the investigation of the relevant literature. Here the researchers examined the correlation between trust and the variables by conducting a questionnaire to a group of managers and other significant employees. The participants included six prestigious UK companies: · Banks - Barclays and TSB · Department stores - Marks and Spencer and Littlewoods · Manufacturers of domestic appliances - Hoover and Philips The enthusiastic responses revealed that most of the twenty-two variables confirmed the correlation to trust. The consequence of the rapid growth of e-commerce has led to an escalation in online retailers. However, this has opened awareness to specific issues of privacy and security amongst internet shoppers whose reluctance and reticence seemingly affects trust towards online retailers. In my proposed scheme, we used Michell et al research on trust as our model system, which was dedicated towards exploring the extent of consumer trust online between two countries, namely the United Kingdom (UK) and Malaysia. The author designed and formulated a questionnaire based around the twenty-two variables that comprises trust. The questionnaire was setup online, and responses were solicited and compiled via email invitations to e-commerce groups and forums in both the UK and Malaysia. The respondents were frequent users of the internet facilities and their experience revealed quantitative facts and figures having high explanatory powers in both countries by the high adjusted R2 after regressions of the variables in the four dimensions. The structure and framework was designed to extricate current attitudes of the internet users towards trust in online retailers between the two countries. Despite time limitations to carry out the project to its full potential, the outcome is encouragingly revealing in terms of comparative trust equations between the countries namely United Kingdom and Malaysia. The author concludes that trust in terms of attitudes and ethnicity needs to be explored further in the growing and changing acceptance of the diminishing use of currency and the projected use of e-financing which is the new proxy to the flexible plastic card.